Alisol B 23-Acetate Ameliorates Azoxymethane/Dextran Sodium Sulfate-Induced Male Murine Colitis-Associated Colorectal Cancer via Modulating the Composition of Gut Microbiota and Improving Intestinal Barrier - Zhu, Huai-Chang; Jia, Xiao-Kang; Fan, Yong; Xu, Shao-Hua; Li, Xiao-Yan; Huang, Ming-Qing; Lan, Meng-Liu; Xu, Wen; Wu, Shui-Sheng (Frontiers in Cellular and Infection Microbiology, 2021)
Hunting for natural compounds that can modulate the structure of the intestinal flora is a new hotspot for colitis‐associated cancer (CAC) prevention or treatment. Alisol B 23-acetate (AB23A) is a natural tetracyclic triterpenoid found in Alismatis rhizoma which is well known for dietary herb. Alismatis rhizoma is often used clinically to treat gastrointestinal diseases in China. In this study, we investigated the potential prevention of AB23A in male mouse models of azoxymethane (AOM) and dextran sulfate sodium (DSS)-induced CAC. AB23A intervention alleviated the body weight loss, disease activity index, colon tumor load, tissue injury, and inflammatory cytokine changes in CAC mice. AB23A intervention leads to remarkable reductions in the activation of TLR, NF-κB and MAPK. AB23A significantly decreased the phosphorylation of p38, ERK, and JNK and up-regulated mucin-2 and the expression of tight junction proteins. The gut microbiota of AB23A-interfered mice was characterized with high microbial diversity, the reduced expansion of pathogenic bacteria, such as Klebsiella, Citrobacter, and Akkermansia, and the increased growth of bacteria including Bacteroides, Lactobacillus, and Alloprevotella. These data reveal that AB23A has the potential to be used to treat CAC in the future.